1994
DOI: 10.1113/expphysiol.1994.sp003748
|View full text |Cite
|
Sign up to set email alerts
|

Role of fetal sac fluids during maternal water deprivation in sheep

Abstract: SUMMARYOur aim was to determine the importance of amniotic and allantoic fluids for the maintenance of fetal plasma composition during maternal dehydration when water transfer from mother to fetus is likely to be reduced. Eight pregnant ewes were studied before, during and after water deprivation (36 h), firstly with the fetal fluid sacs intact and then with them drained of fluid for 5 days. When water deprivation was combined with drainage, the increases in the osmolalities, [Na+] and [Cl-] in maternal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The inhibitory effects of maternal heating and maternal water deprivation on fetal lung liquid production were additive, rather than synergistic. We have previously suggested that the increase in fetal plasma osmolality may be partly responsible for the decline in lung liquid production with maternal water deprivation (Dickson & Harding, 1994). We have shown that the effects of maternal heating and water deprivation on fetal urinary osmolality, but not the decrease in urine production, were synergistic rather than additive.…”
Section: Maternal Heat Stress Combined With Water Deprivationmentioning
confidence: 77%
See 3 more Smart Citations
“…The inhibitory effects of maternal heating and maternal water deprivation on fetal lung liquid production were additive, rather than synergistic. We have previously suggested that the increase in fetal plasma osmolality may be partly responsible for the decline in lung liquid production with maternal water deprivation (Dickson & Harding, 1994). We have shown that the effects of maternal heating and water deprivation on fetal urinary osmolality, but not the decrease in urine production, were synergistic rather than additive.…”
Section: Maternal Heat Stress Combined With Water Deprivationmentioning
confidence: 77%
“…Daily rates of Na+, K+ and Cl-excretion in fetal urine and secretion in lung liquid have been adjusted for fetal body weight (Dickson & Harding, 1994).…”
Section: Sampling Of Body Fluidsmentioning
confidence: 99%
See 2 more Smart Citations